The cryo-EM structure of homotetrameric attachment glycoprotein from langya henipavirus - Yingying Guo; Songyue Wu; Wenting Li; Haonan Yang; Tianhao Shi; Bin Ju; Zheng Zhang; Renhong Yan (Nature Communications, 2024)
Abstract Langya Henipavirus (LayV) infection is an emerging zoonotic disease that has been causing respiratory symptoms in China since 2019. For virus entry, LayV’s genome encodes the fusion protein F and the attachment glycoprotein G. However, the structural and functional information regarding LayV-G remains unclear. In this study, we revealed that LayV-G cannot bind to the receptors found in other HNVs, such as ephrin B2/B3, and it shows different antigenicity from HeV-G and NiV-G. Furthermore, we determined the near full-length structure of LayV-G, which displays a distinct mushroom-shaped configuration, distinguishing it from other attachment glycoproteins of HNV. The stalk and transmembrane regions resemble the stem and root of mushroom and four downward-tilted head domains as mushroom cap potentially interact with the F protein and influence membrane fusion process. Our findings enhance the understanding of emerging HNVs that cause human diseases through zoonotic transmission and provide implication for LayV related vaccine development.